Lightning energy conversion using lasers. - Nasrullah, K.; Mariun, Norman
Potential energy sources are being investigated for the socioeconomic needs and increased power demand. Systems employing nuclear, thermal, hydro, solar, volcano, MHD, tidal and wind power generation techniques already exist. This work describes our attempt to utilize the off-planet lightning charge to store super electrolytic batteries or super capacitors. The electrostatic charge on clouds can be shifted to earth through a conductive air plasma channel created by appropriate high power Q-Switched and mode-locked laser. The pulsed laser may create a conducting path consisting of ionized air particles from earth to some upper atmosphere. An antenna connected to anode of super cell or positive terminal of the super capacitor will accumulate and store this charge for future use. The anode of battery or positive terminal of capacitor may be connected to earth to complete the circuit. Due to extremely aloud thundering and tropical weather severity a detailed work was done on lightning regarding its temporal and spatial profiles to develop a reasonable model to explore transient charging characteristics. Experimental work in respect of laser inducted plasma wire creation and charging capabilities of super storage batteries or super capacitors is optimized. Latest experimental results are reported.